Eksplorasi Desain TPACK dalam Pengembangan Smart Hydroponic System Berbasis IoT sebagai Media Peningkatan Kemampuan STEM Siswa - Nove Kurniati Sari; Zulhafandi Zulhafandi; Banyuriatiga Banyuriatiga; Syaddam Syaddam (Jurnal Terapan Teknologi Informasi, 2026)
STEM education is an interdisciplinary approach that integrates various disciplines to equip Students to face the challenges of the digital era and the Industrial Revolution 4.0. The success of this innovative learning implementation depends on how a teacher designs a cohesive instructional scenario. In designing STEM learning that integrates the latest technology, Teachers need specific competencies outlined in the TPACK framework. The purpose of this research is to develop a learning design model based on the TPACK framework that integrates STEM approaches via IoT instruments, using a case study of the Smart Hydroponic System project, to hone Students' computational thinking logic using block code. In the research method employed, qualitative descriptive and experimental technical approaches with exploratory characteristics are used. This study succeeded in formulating seven elements of TPACK to convert complex STEM materials into "Playing Logic" activities that align with the cognitive capacity of elementary school Students. The development of the Arduino- and Tinkercad-based prototypes demonstrated the overall functionality of all components through black-box testing. The integration of IoT with the Project-Based Learning approach, as documented in the literature, has proven effective in transforming abstract concepts into concrete, interactive experiences without requiring mastery of complex textual programming. Overall, this framework provides practical solutions for Teachers/Educators in creating an exploratory STEM learning ecosystem, while significantly improving Students' computational thinking skills.